The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5007/1980-0037.2010v12n1p62
|View full text |Cite
|
Sign up to set email alerts
|

Índice de tensão específica dos flexores do cotovelo em homens treinados e não treinados DOI:10.5007/1980-0037.2010v12n1p62

Abstract: Rev Bras Cineantropom Desempenho Hum 2010, 12(1):62-67Resumo -O índice de tensão específica (ITE) estima a relação entre o torque máximo (TQ) e o volume muscular (VM) para uma tarefa específica, e inclui a espessura muscular (EM) como um parâmetro medido diretamente pela ultrassonografia. O objetivo do presente estudo foi comparar o VM, TQ e ITE dos flexores do cotovelo entre indivíduos treinados e não treinados em força. Participaram do estudo 40 homens, sendo 11 treinados em força há pelo menos dois anos [gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ultrasonography has lately been used in research as a way to assess muscle damage and the muscle volume 6,8 . Studies have applied this technique both in trained subjects as untrained by the assessment of muscle thickness, which variation was associated with the occurrence of edema in the post-workout period 9,10 . Several studies 1,[11][12][13] already reported the response of many biomarkers after strength training, but studies using low cost diagnostic imaging tools (as ultrasonography and thermography) are rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has lately been used in research as a way to assess muscle damage and the muscle volume 6,8 . Studies have applied this technique both in trained subjects as untrained by the assessment of muscle thickness, which variation was associated with the occurrence of edema in the post-workout period 9,10 . Several studies 1,[11][12][13] already reported the response of many biomarkers after strength training, but studies using low cost diagnostic imaging tools (as ultrasonography and thermography) are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 1,[11][12][13] already reported the response of many biomarkers after strength training, but studies using low cost diagnostic imaging tools (as ultrasonography and thermography) are rare. authors 14 have reported a high correlation in the diagnosis of handle repetitive strain injuries (RSI) and work-related musculoskeletal disorders (WMSD) between the assessment by ultrasound and thermography, however, although there are studies evaluating muscle recovery through ultrasound 9,10 or by thermography 1,4 in isolation but there is no known correlation between the results of these assessment tools in the muscular aguda ( post-workout period or the best period to use one or another. Thus, the aim of this study was to evaluate the usage of skin temperature and muscle thickness (MT) to monitoring the muscle response (until 96 hours) to high-intensity strength training.…”
Section: Introductionmentioning
confidence: 99%
“…The MVIC test was previously described 18,19 . Maximal load isometric test was used for the elbow flexors (EF) and elbow extensors (EE).…”
Section: Maximal Voluntary Isometric Contraction (Mvic)mentioning
confidence: 99%